just differentiate each part so you get 16x + 26y(dy/dx) - 10y -10x(dy/dx)= 0
everytime you differntiate a y put in dy/dx after it, when differntiating the -10xy just use the product rule to get -10x(dy/dx)-10y.
to simplify take everything that isnt with dy/dx to get:-
26y(dy/x)-10x(dy/dx)=10y-16x,
take out a factor of dy/dx ont he lhs
dy/dx(26y-10x)=10y-26x
just bring it over to ther otehr side
dy/dx=(10y-26x)/(26y-10x)
Thats it i think although id get someone to check, im prone to making stupid mistakes.